TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP JAMINAN PADA INVESTASI DIGITAL CYRONIUM COIN - Pratama, Zenda; Hidayat, Fatah; Lubis, Ramiah (Program Studi Muamalah Fakultas Syariah dan Hukum, 2020)
This thesis is entitled Review of Sharia Economic Law of Guarantee on Cyronium Coin Investment. Against the background of the problem, namely the effect of physical gold coin collateral on Cyronium Coin digital investment which can ensure the security of these investment activities. The formulation of the problem, namely: What is the guarantee on Cyronium Coin digital investment? and How does Sharia Economic Law review the guarantee on Cyronium Coin digital investment ?. This type of research is library research, the primary data of which is obtained from a review of literature studies and from the official website of Cyronium Coin. The data obtained were analyzed qualitatively, namely by producing descriptive data. which applies to reality as the primary material associated with the theories in secondary data. Based on data analysis, deductive conclusions can be drawn in accordance with the formulation of the problem. The results of the study concluded: First, the guarantee on Cyronium Coin digital investment is based on the procedure, Cyronium coins have a selling value according to the price of 20 grams of gold. Its function is to maintain prices so that CYRO tokens can protect investors' funds. Investors who purchase CYRO tokens can choose two options, including choosing to have assets in the form of CYRO tokens and choosing to have assets in the form of Cyronium physical coins where the physical coins are used as collateral for investment. Second, the Sharia Economic Law Review of Guarantee on Cyronium Coin Digital Investment shows that in this case, the consent granted in the implementation of the agreement between the investor and Cyronium is marked by the approval of the investor who has registered and fulfills the terms and conditions that have been made by Cyronium. Then the guarantor is Cyronium, the recipient of the guarantee is the investors, the goods that are used as the object of collateral are Cyronium's physical coins. In its implementation, it has fulfilled the pillars and requirements of kafalah / dhaman as previously explained and this guarantee does not conflict with Islamic law. Keywords: Guarantee, Digital Investment, Cyronium Coin.